Partisipasi Masyarakat Dalam Pembangunan Desa Sarimulya Kecamatan Kota Baru Kabupaten Karawang - Rifa Ahda Kanita; Lina Aryani; Maulana Rifai; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Community participation is one of the important elements in determining the success or failure of the development goals of an area can be achieved or vice versa. However, the active participation of the community has not been fully implemented at every stage of development in an area. The research method used in this study is a qualitative method that focuses on meaning, in-depth analysis and interpretation of researchers as research instruments. This study uses a descriptive approach because this study analyzes and describes social problems, namely how the role of community participation in development in Sarimulya Village, Kota Baru District, Karawang Regency. From the results of research that has been carried out, the participation of the people of Sarimulya Village in terms of decision making, implementation of development, and taking benefits can be said to be quite good. However, in terms of evaluating the development of community participation, it can be said that it is not good enough because the community is not directly involved in village evaluation meetings.